2017
DOI: 10.1016/j.jphotobiol.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Radicals formed from proton loss of carotenoid radical cations: A special form of carotenoid neutral radical occurring in photoprotection

Abstract: In an organized assembly in Arabidopsis thaliana plant, proton loss from the radical cation of zeaxanthin (Zea) was found to occur under intense illumination, a possible component in photoprotection. A stable neutral radical is formed because of the favorable proton loss at C4(4') position(s) of the terminal ends of Zea that extends the unpaired spin density distribution (notation Zea(4) or Zea(4') by symmetry). Proton loss from the radical cation of β-carotene (β-car) to available proton acceptors was also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…It should be noted that this work established the optical absorption spectrum for the neutral species without using transient absorption spectroscopy. This assignment of the neutral species in the absence of oxygen was confirmed via studies of the effect of pH and this species was linked to a previously unassigned peak reported from spectral studies of Photosystem II (PSII) [ 69 ]. The Kispert group speculate that in PS II itself photoprotection can arise both by the loss of the excess vibrational energy of the radical cation and by quenching of excited chlorophyll by the carotenoid proton loss neutral radical.…”
Section: Carotenoidssupporting
confidence: 61%
See 3 more Smart Citations
“…It should be noted that this work established the optical absorption spectrum for the neutral species without using transient absorption spectroscopy. This assignment of the neutral species in the absence of oxygen was confirmed via studies of the effect of pH and this species was linked to a previously unassigned peak reported from spectral studies of Photosystem II (PSII) [ 69 ]. The Kispert group speculate that in PS II itself photoprotection can arise both by the loss of the excess vibrational energy of the radical cation and by quenching of excited chlorophyll by the carotenoid proton loss neutral radical.…”
Section: Carotenoidssupporting
confidence: 61%
“…A recent review [ 67 ] has highlighted a significant apparent disagreement concerning the fate of β-carotene radical cation. El-Agamey and co-workers [ 68 ] studied the effect of pH on the decay of the β-carotene radical cation (HCAR •+ ) while the extensive work of Kispert and co-workers used advanced electron paramagnetic resonance techniques and optical measurements beside electrochemical and theoretical studies [ 67 , 69 , 70 , 71 ]. The Kispert group showed that proton loss from β-carotene radical cation leads to the neutral carotenoid radical (CAR • ) HCAR •+ → CAR • + H + with an absorption maximum around 750 nm.…”
Section: Carotenoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carotenoid radicals such as radical cations (Car • + ) formed by electron transfer from carotenoid molecules (see Figure 4 ) and proton loss neutral radicals #Car • formed under high light intensity by deprotonation of Car • + at the most favorable position have been found to occur not only in solution, but in photosynthetic media. The proton loss neutral radical, first observed to occur in irradiated PSII samples as #β-Car • (beta-carotene neutral radical) [ 23 ] and then in the Arabidopsis thaliana plant [ 24 ] as #Zea • (zeaxanthin neutral radical), has been suggested [ 25 , 26 ] to provide additional photo protection of plants to that provided by Car • + . Since the radical cation Zea • + is a weak acid (with pK a 4–7), loss of a proton will occur to a water acceptor and the proton loss neutral radical, #Zea • , is formed.…”
Section: Unique Properties Of Astaxanthinmentioning
confidence: 99%